1997
DOI: 10.1126/science.277.5329.1081
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity up to 126 Kelvin in Interstitially Doped Ba 2 Ca n - 1 Cu n O x [02( n -1) n -Ba]

Abstract: M NaC 10 mM phosphate. pH 7.0) were mlxed, Acids Res. 16, 4937 (1 988)l. frozen (40 s), thawed (5 mni, and spotted with a 18. We acknowledge suppot? by grants from the Nationcapillary tube on a C, , TLC plate A blue spot deve-al Institute of General Medical Sc~ences (GM 10265) oped, In the absence of target, the color remaned and the Offce of Naval Research (NO01 4-94-1 -0703 pnk. For comparison, the lower Imlt for detectng an and N00014-97-10430) and the Department of De-ol~gonucleot~de with the use of a prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 11 publications
(1 reference statement)
1
5
0
2
Order By: Relevance
“…The maxima are tolerable considering the high electron densities already present at the AE2 site. This highpressure synthesis study agrees with previous reports concerning mixed sites (Chu et al, 1997;Wu et al, 1998), i.e. Cu as well as Ca enter the CR and Tl can be found at the AE1 site.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The maxima are tolerable considering the high electron densities already present at the AE2 site. This highpressure synthesis study agrees with previous reports concerning mixed sites (Chu et al, 1997;Wu et al, 1998), i.e. Cu as well as Ca enter the CR and Tl can be found at the AE1 site.…”
supporting
confidence: 93%
“…Both Tl and Hg were earlier observed at the AE1 site in a high-pressure synthesized 2212-type phase (Wu et al, 1998), however, Wu et al reported this as a new stacking order. The CR on the other hand was occupied by both Ca and Cu in another superconducting material, also formed under high-pressure conditions (Chu et al, 1997). Since our crystal was synthesized under pressure as well, Ca was introduced at the CR site at the same time as a minor amount of Tl was placed at the AE1 site.…”
mentioning
confidence: 99%
“…成的T c 推高到126 K [16] , 接近常压T c 最高的Hg1223 [4] . 通过与赵忠贤老师合作, 我们表征了"铜系"和 "卤系"铜基超导材料的临界电流密度性能 [10] , 如图 7所示"铜系"和"卤系"具有优良的高温临界电流密度 特性.…”
Section: 如图6示 高压制备的Cu1234在常压的超导转变unclassified
“…[2,6] Cuprate superconductors with high superconducting transition temperatures (T c s) could also be considered as typical lamellar oxides, in which the superconducting CuO 2 blocks are regularly interstratified with charge-reserving blocks. [7] However, it is well known that their interlayer bonding characteristics are strongly covalent, with the exception of Bi-based superconductors [8] whose properties are closely related to the different electronic configurations of the component metal ions.…”
mentioning
confidence: 99%